2017
DOI: 10.1007/s00259-017-3665-9
|View full text |Cite
|
Sign up to set email alerts
|

Repeated PSMA-targeting radioligand therapy of metastatic prostate cancer with 131I-MIP-1095

Abstract: PurposeProstate-specific membrane antigen (PSMA)-targeting radioligand therapy (RLT) was introduced in 2011. The first report described the antitumor and side effects of a single dose. The aim of this analysis was to evaluate toxicity and antitumor activity after single and repetitive therapies.MethodsThirty-four men with metastatic castration-resistant prostate cancer received PSMA-RLT with 131I-MIP-1095. Twenty-three patients received a second, and three patients a third dose, timed at PSA progression after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 33 publications
1
52
0
Order By: Relevance
“…42,43 Figure S4), which are in agreement with other studies that have examined the binding of PSMA ligands to PSMA-positive cells. [44][45][46] Gourni et al showed that [ 11 In]In-PSMA-617 to LNCaP cells yielded a k d of 5.4 nM. 44 Umbricht et al reported that [ 177 Lu]Lu-PSMA-617, [ 44 Sc]Sc-PSMA-617 and [ 68 Ga] Ga-PSMA-617 to PC-3 PIP cells gave the k d values of 39, 33 and 72 nM, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…42,43 Figure S4), which are in agreement with other studies that have examined the binding of PSMA ligands to PSMA-positive cells. [44][45][46] Gourni et al showed that [ 11 In]In-PSMA-617 to LNCaP cells yielded a k d of 5.4 nM. 44 Umbricht et al reported that [ 177 Lu]Lu-PSMA-617, [ 44 Sc]Sc-PSMA-617 and [ 68 Ga] Ga-PSMA-617 to PC-3 PIP cells gave the k d values of 39, 33 and 72 nM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The most studied PSMA ligands for therapeutic use, PSMA‐617 and PSMA‐I&T, have different linkers, while the binding motif (glutamate‐urea moiety) and the chelating moiety (1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetraacetic acid [DOTA]) are the same. PSMA‐617 and PSMA‐I&T labelled with the beta emitter 177 Lu ( t 1/2 ≈6.7 days) and MIP‐1095 labelled with the beta emitter 131 I ( t 1/2 ≈8.0 days) have been investigated in preclinical and clinical studies . A recent meta‐analysis of 17 studies demonstrated that RLT with [ 177 Lu]Lu‐PSMA‐617 and [ 177 Lu]Lu‐PSMA‐I&T is an effective treatment for mCRPC with low toxicity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most serious clinical problem is that in the course of treatment PC becomes refractory to hormone manipulation, known as metastatic castration-resistant prostate cancer (mCRPC) [2,4]. There are many options for the treatment of mCRPC including docetaxel, abiraterone acetate, enzalutamide, cabazitaxel, radium-223, Sipuleucel-T (the only cancer vaccine approved to treat advanced PC so far) [3,4,5,6,7,8], and radioligand therapy (RLT) directed against prostate-specific membrane antigen PSMA, which could be successfully used as a third line therapy of mCRPC [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Ligands labeled with the b-emitting 177 Lu, such as 177 Lu-prostate-specific membrane antigen (PSMA) 617 (2)(3)(4)(5)(6) and 177 Lu-PSMA-I&T (7)(8), have been shown to induce at least a 50% decrease in PSA in 30%-60% of patients after a single cycle or multiple cycles of therapy, with only mild-to-moderate, reversible side effects evident even after multiple therapy cycles. Other ligands labeled with the b-emitting 131 I, such as 131 I-MIP-1095, have induced even more dramatic responses, though the reported side effects were more severe (9)(10).…”
mentioning
confidence: 99%